2004
DOI: 10.30843/nzpp.2004.57.6931
|View full text |Cite
|
Sign up to set email alerts
|

The impact of tall fescue (<i>Festuca arundinacea</i>) endophyte (<i>Neotyphodium</i> spp) on non target soil microorganisms

Abstract: The impact of two strains of the tall fescue (Festuca arundinacea) endophyte (Neotyphodium spp) (E) on the rhizoplane and rhizosphere soil microorganisms was examined at two sites (Lincoln endophytefree (E) and the endophyte strain AR501; and Aorangi E AR501 and a second strain AR542) Rhizosphere and rhizoplane populations of bacteria and fungi functional diversity root fungi and soil microbial biomass carbon and nitrogen were measured Most characteristics measured showed no differences between E and E samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…In the case of the two sites here, the nematode community indicated that the decomposition pathway in these soils was predominantly fungal. This was borne out by the populations of fungi detected by Sayer et al (2004) from the same soil samples. Although bacterial populations still dominated these soil samples there were higher populations of fungi detected than is normally expected from pastoral soils and this is perhaps explained by the dry soil conditions prior to, and at, the time of sampling.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the case of the two sites here, the nematode community indicated that the decomposition pathway in these soils was predominantly fungal. This was borne out by the populations of fungi detected by Sayer et al (2004) from the same soil samples. Although bacterial populations still dominated these soil samples there were higher populations of fungi detected than is normally expected from pastoral soils and this is perhaps explained by the dry soil conditions prior to, and at, the time of sampling.…”
Section: Discussionmentioning
confidence: 96%
“…To investigate any such effects, two fi eld sites, which form part of the AgResearch National Endophyte Evaluation trial, were sampled to determine the impact of endophyte infection in tall fescue on the soil biota. Soil and root samples were examined for microbes (Sayer et al 2004), mycorrhizal fungi and insects (Popay & Jensen 2005), as well as the nematode populations reported here.…”
Section: Introductionmentioning
confidence: 99%
“…Live and uninjured grass grub were retained and later weighed. After removing subsamples for quantifi cation of micro-organisms (Sayer et al 2004) and nematodes (Bell 2005), roots and soil from each plot were subjected twice to a wet sieving process to extract small invertebrates. Material that was captured on both the 210 µm and 710 µm aperture sieves during each wet sieving was washed into separate specimen containers and refrigerated until counting.…”
Section: Invertebratesmentioning
confidence: 99%
“…These fungi can increase the ability of plants to forage for nutrients in soil, although grasses show little reliance on AM except under phosphorous-limiting conditions. Sayer et al (2004) and Bell (2005) have reported on, respectively, the micro-organisms and nematodes found in roots and soil samples taken from the tall fescue plots at two of the fi eld trial sites, Aorangi near Palmerston North and at Lincoln in Canterbury. In this paper information is presented on soil invertebrates, other than nematodes, that were taken from the same samples and the presence of AM in the roots.…”
Section: Introductionmentioning
confidence: 99%
“…Endophyte has also been shown to have an impact on insects, nematodes, ruminant mammals, other fungi (Liu et al 2011) and plants (Schardl et al 2004) and earthworms (Humphries et al 2001). However, there is little known about their effects on soil bacterial populations (Omacini et al 2004;Sayer et al 2004).…”
Section: Introductionmentioning
confidence: 99%